2014
DOI: 10.1097/nmd.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Attention Deficit Hyperactivity Disorder in Adults From a French Community Sample

Abstract: Validated tools are lacking in languages such as French to diagnose attention deficit hyperactivity disorder (ADHD) in adults. The Adult ADHD Symptoms Self-Report (ASRS) was filled out by 1171 parents of 900 school-aged youths in the context of the Children and Parents With ADHD and Related Disorders study. Prevalence estimates based on three scoring methods are compared (6-item screener, all 18 items, or the screener followed by the 12 remaining items). On the basis of the recommended and more conservative sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 75 publications
8
37
0
Order By: Relevance
“…The results are nonetheless comparable to those obtained in studies that examined the prevalence of adult ADHD in the general population (Fayyad et al, 2007;Caci et al, 2014).…”
Section: Limitationssupporting
confidence: 87%
See 1 more Smart Citation
“…The results are nonetheless comparable to those obtained in studies that examined the prevalence of adult ADHD in the general population (Fayyad et al, 2007;Caci et al, 2014).…”
Section: Limitationssupporting
confidence: 87%
“…This percentage exceeds the prevalence of adult ADHD in the worldwide general population, which stands at 2.5% (American Psychiatric Association, 2013), and in the French general population, which has been estimated at 2.99% (Caci et al, 2014). In their study using solely the ASRS-V1.1, Caci et al (2014) reported a prevalence rate for adult ADHD of 11.27% in the French general population, which is far less than the rate observed in our study, i.e., 18.33%, on the basis of this same instrument. The rates are also higher than the prevalence rate of 7.3% reported by Fayyad et al (2007) in the French general population.…”
Section: Discussionmentioning
confidence: 94%
“…Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent psychiatric disorders with estimated prevalence ranging from 3% to 5% in adults (Faraone and Biederman, 2005;Fayyad et al, 2007), with a 2.99% prevalence in France (Caci et al, 2014). Depending on the number of inattention, hyperactivity or impulsivity symptoms, the diagnostic formulation, as specified by the Diagnostic and Statistical Manual of Mental Disorders 4th edition, text revision (DSM-IV-TR) (American Psychiatric Association, 2000), includes three distinct subtypes: (1) ADHD Predominantly Inattentive (ADHD-PI), (2) ADHD Predominantly Hyperactive/Impulsive,(ADHD-HI) and (3) ADHD Combined (ADHD-C) subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…It is also common in adults, with estimates varying from 2.8% to 4.7% [6][7][8]. People with ADHD have impaired functioning due to difficulties with sustaining attention and with controlling impulsive behaviour [9].…”
Section: What Is Adhd?mentioning
confidence: 99%